GEMAR MENABUNG GENERASI GEN Z: TANTANGAN DAN STRATEGI - Bahruddin Ashuri; Ilham Khalid; Syahroni Syahroni; Zul Hendri; Khodijah Ishak; Fitriasari Sintarini (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Generation Z is a group born in the digital era, where access to information and technology is very easy. However, saving habits in this generation are still a challenge that needs to be considered. This article aims to examine the saving habits of generation Z, the factors that influence them, and strategies that can be applied to increase awareness and saving habits in this generation. The research method used is a literature study from various trusted sources and direct observation at MAN 1 Plus Keterampilan Bengkalis. The results of the study show that the main factors influencing Gen Z's saving habits are a consumptive mindset, the influence of social media, and the lack of financial education from an early age. Therefore, strategies are needed such as digital-based financial education, the development of attractive financial applications, and the active role of families and educational institutions in instilling saving habits. By implementing this strategy, it is hoped that generation Z can be more aware of the importance of saving for a better future.